2009
DOI: 10.1016/j.virol.2008.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Role of regulatory T cells in coronavirus-induced acute encephalitis

Abstract: C57BL/6 mice infected with mouse hepatitis virus, strain JHM (JHMV) develop a rapidly fatal acute encephalitis. Previously, we showed that this disease is partially CD4 T cell-mediated since infection with a recombinant JHMV (rJ) mutated in only a single immunodominant CD4 T cell epitope (epitope M133, rJ.MY135Q) results in a nonlethal disease. Increased mortality correlated with a greater number of JHMV-specific CD4 T cells in the brains of rJ compared to rJ.MY135Q-infected mice. Here, we extend these results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 47 publications
4
87
0
Order By: Relevance
“…In contrast, when SJL/J mice were treated with iTregs during the late phase of TMEV infection (iTreg-late), iTreg-late SJL/J mice developed less CNS inflammatory demyelination and a greater amount of IL-10 production, compared with untreated control mice. Here, IL-10 was produced from multiple cell types, including CD4 + and CD8 + T cells, B cells, macrophages, and DCs, which was consistent with the findings that Tregs could induce IL-10 production from other cell types (Anghelina, Zhao, Trandem, & Perlman, 2009;Kearley, Barker, Robinson, & Lloyd, 2005). The contrasting effects of iTregs in TMEV infection suggested that Tregs could be beneficial by suppressing immunopathology, when CNS viral loads were low (iTreg-late) as seen with persistent viral infection, while Tregs could be detrimental by suppressing antiviral immunity, when viral replication is active (iTreg-early) as in acute viral infection.…”
Section: Role Of Tregssupporting
confidence: 89%
“…In contrast, when SJL/J mice were treated with iTregs during the late phase of TMEV infection (iTreg-late), iTreg-late SJL/J mice developed less CNS inflammatory demyelination and a greater amount of IL-10 production, compared with untreated control mice. Here, IL-10 was produced from multiple cell types, including CD4 + and CD8 + T cells, B cells, macrophages, and DCs, which was consistent with the findings that Tregs could induce IL-10 production from other cell types (Anghelina, Zhao, Trandem, & Perlman, 2009;Kearley, Barker, Robinson, & Lloyd, 2005). The contrasting effects of iTregs in TMEV infection suggested that Tregs could be beneficial by suppressing immunopathology, when CNS viral loads were low (iTreg-late) as seen with persistent viral infection, while Tregs could be detrimental by suppressing antiviral immunity, when viral replication is active (iTreg-early) as in acute viral infection.…”
Section: Role Of Tregssupporting
confidence: 89%
“…Further, virus-specific Tregs express both IFN-c and IL-10 suggesting immune regulatory capacities mediated through cytokines secreted following antigen stimulation. Indeed, virus-specific Tregs dampen proliferation of virus-specific effector CD4 + T cells, and depletion of Tregs increases mortality (2,102). These data suggest that within the context of acute JHMV-induced neurologic disease, Tregs limit immunopathological CNS disease without negatively impacting viral clearance (2).…”
Section: Figmentioning
confidence: 95%
“…i.c., intracranial; NK, natural killer. More recently, Perlman and colleagues have provided important insight into the functional role of regulatory T cells (Tregs) during acute JHMV-induced CNS disease (2,102). Tregs are detected within the CNS at the same time as effector CD4 + T cells, indicating that the emergence and accumulation of both populations of cells are on a similar timeline following viral infection.…”
Section: Figmentioning
confidence: 99%
“…33 Induced Tregs in coronaviral infection also protects against greater severity of the disease. 34 Anghelina et al 35 showed that Tregs depletion resulted in increased mortality in coronavirus-induced acute encephalitis, and transfer of Tregs increased survival from 0% to 50%. At the moment, the association between Tregs and airway infection is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…8e10 Huang et al 8 showed that IL-4, IL-5, and IL-13 in BALF were inhibited by administration of plasmid DNA encoding recombinant single-chain IL-35. Dong et al 9 also reported that administration of recombinant fusion protein of murine IL- 35 and human Fc fragment (rIL-35) reduced eosinophil counts in BALF. Li et al 10 documented a reduction in the numbers of inflammatory cells and levels of IL-4, IL-5, IL-13, and IL-17 in BALF with administration of adenovirus expressing IL-35.…”
Section: Introductionmentioning
confidence: 99%